MODELAGEM E OTIMIZAÇÃO PARA PLANEJAMENTO DE TRANSPORTE DE PASSAGEIROS COM RESTRIÇÕES DE CUSTO E QUALIDADE DE SERVIÇO. - MARQUES, José Artur Lima Cabral (2012)
This master dissertation presents a optimization mathematical programming model derived from the classical problem of transport, which aims to scale, with global optimization, the fleet of a system of road passenger transport, describing possible routes between each source/target to meet the constraints of cost (profitability) and quality of service. It covers classic methods of solution of linear programming models considered streaming networks and proposes improvements to the canonical model of the transport problem from the perspective of transit planning, and analyze the use of dynamic programming, evolutionary methods and heuristics for solving the problem of minimization of the model.